OP0053 SECUKINUMAB IMPROVES CLINICAL AND IMAGING OUTCOMES IN PATIENTS WITH PSORIATIC ARTHRITIS AND AXIAL MANIFESTATIONS WITH INADEQUATE RESPONSE TO NSAIDS: WEEK 52 RESULTS FROM THE MAXIMISE TRIAL. (2nd June 2020) - Baraliakos, X.; Gossec, L.; Pournara, E.; Jeka, S.; Blanco, R.; D'angelo, S.; Schett, G.; Schulz, B.; Rissler, M.; Nagar, K.; Perella, C.; Coates, L. C.
Abstract : Background: Although axial disease may affect up to 70% of patients (pts) with Psoriatic Arthritis (PsA), evidence on the efficacy of biologics in the treatment of axial manifestations in such pts is limited, 1 particularly as validated classification criteria for this subtype of PsA are not yet available. MAXIMISE (NCT02721966 ) is the first randomised controlled trial evaluating the efficacy of a biologic in the management of the axial manifestations of PsA and showed that secukinumab (SEC) 300 and 150 mg provided rapid and significant improvement in ASAS20 responses in these pts through week (Wk) 12. 2 Objectives: To present 52 wks efficacy results and imaging data from the MAXIMISE trial. Methods: This phase 3b, double-blind, placebo (PBO)-controlled, multicentre 52-wk trial included 498 pts (aged ≥18 years) with a diagnosis of PsA and classified by CASPAR criteria, spinal pain VAS score ≥ 40/100 and BASDAI score ≥ 4 despite use of at least two NSAIDs. Pts were randomised to SEC 300 mg (N=167) or SEC 150 mg (N=165) or PBO (N=166) wkly for 4 wks and every 4 wks thereafter. At Wk 12, PBO pts were re-randomised to SEC 300/150 mg. The primary endpoint was ASAS20 response with SEC 300 mg at Wk 12. The key secondary endpoint was ASAS20 response with SEC 150 mg at Wk 12. Wk 52 data are presented as observed. Bone marrow oedema of the entire spine and sacroiliac joints were assessed centrally with Berlin MRI scores at Baseline, Wk 12 and Wk 52. Results: Primary and key secondary endpoints were met; ASAS20 responses were sustained and increased further through Wk 52. 75%/79.7% of the PBO pts re-randomised at Wk 12 to SEC 300/150 mg achieved ASAS20 response at Wk 52 (Figure 1 ). ASAS40 responses at Wk 52 were 69.1% [SEC 300 mg], 64.5% [SEC 150 mg], 62.5% [PBO-SEC 300 mg], and 54.1% [PBO-SEC 150 mg]. At baseline, 59.5% [SEC 300 mg], 53.5% [SEC 150 mg] and 64.2% [PBO] of the pts had positive MRIs for the sacroiliac joints and/or the spine with Berlin MRI score ≥1. The reductions of Berlin MRI score for entire spine and sacroiliac joints were statistically significant for pts treated with SEC 300/150 mg vs. placebo (Figure 2 a and b ). There were no new or unexpected safety findings. Conclusion: Secukinumab improved all evaluated ASAS responses through Wk 52 in PsA pts with axial manifestations and inadequate responses to NSAIDs and led to significant reduction of inflammatory MRI lesions in the spine and the Sacroiliac Joints. The safety profile of secukinumab through Wk 52 was consistent with previous reports. 3-4 References: [1]McInnes IB, et al. Lancet. 2015;386(9999):1137–46. [2]Baraliakos X, et al. Arthritis Rheumatol . 2019;71 (suppl 10). [3]Langley RG, et al. N Engl J Med. 2014;371:326–38. [4]Sieper J, et al. Ann Rheum Dis. 2016;0:1–8. Acknowledgments: The study was sponsored by Novartis Pharma AG, Basel, Switzerland. Disclosure of Interests: Xenofon Baraliakos Grant/research support from: Grant/research support from: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Consultant of: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Speakers bureau: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Laure Gossec Grant/research support from: Lilly, Mylan, Pfizer, Sandoz, Consultant of: AbbVie, Amgen, Biogen, Celgene, Janssen, Lilly, Novartis, Pfizer, Sandoz, Sanofi-Aventis, UCB, Effie Pournara Shareholder of: Novartis, Employee of: Novartis, Sławomir Jeka Grant/research support from: AbbVie, Pfizer, Roche, Novartis, MSD, Sandoz, Eli Lilly, Egis, UCB, Celgene, Speakers bureau: AbbVie, Pfizer, Roche, Novartis, MSD, Sandoz, Eli Lilly, Egis, UCB, Celgene, Ricardo Blanco Grant/research support from: AbbVie, MSD, Roche, Consultant of: Abbvie, Eli Lilly, Pfizer, Roche, Bristol-Myers, Janssen, UCB Pharma and MSD, Speakers bureau: Abbvie, Eli Lilly, Pfizer, Roche, Bristol-Myers, Janssen, UCB Pharma. MSD, Salvatore D'Angelo Consultant of: AbbVie, Biogen, BMS, Celgene, Eli Lilly, MSD, Novartis, and UCB, Speakers bureau: AbbVie, BMS, Celgene, Eli Lilly, Novartis, Pfizer, and Sanofi, Georg Schett Speakers bureau: AbbVie, BMS, Celgene, Janssen, Eli Lilly, Novartis, Roche and UCB, Barbara Schulz Employee of: Novartis, Michael Rissler Shareholder of: Novartis, Employee of: Novartis, Kriti Nagar Employee of: Novartis, Chiara Perella Shareholder of: Novartis, Employee of: Novartis, Laura C Coates: None declared